Acquired dysfibrinogenaemia masquerading as disseminated intravascular coagulation in acute pancreatitis. Issue 6 (June 1988) - Wilde, J T; Thomas, W E; Lane, D A; Greaves, M; Preston, F E
Abstract : Acquired dysfibrinogenaemia as the cause of coagulation abnormalities occurred in a case of acute pancreatitis. Initial coagulation studies showed a prolonged thrombin time and increased concentrations of serum fibrinogen/fibrin degradation products and plasma D-dimer. Further studies on purified fibrinogen showed evidence of degradation of the C-terminal ends of the A-alpha chains, which, it is suggested, resulted from the action of circulating pancreatic proteases. Fibrin polymerisation was thus shown to be impaired, which explains the prolongation of the thrombin time. There was a temporal relation between increased amylase activities and the prolonged thrombin time, both of which returned to normal three weeks after admission. Acquired dysfibrinogenaemia may be an underrecognized phenomenon in acute pancreatitis and may lead to misinterpretation of coagulation test abnormalities.